A critically ill adolescent with EBV-associated hemophagocytic lymphohistiocytosis-induced hyperinflammatory shock: a case report and literature review - Chen, Yong; Zhang, Ruodai; Wang, Chenghu; Ren, Yi (Frontiers in Immunology, 2026)
Epstein-Barr virus (EBV) infection can trigger life-threatening complications, including hemophagocytic lymphohistiocytosis (HLH) and septic shock. The overlapping clinical manifestations of these conditions pose significant diagnostic and therapeutic challenges. This article reports the case of a previously healthy 19-year-old female who presented with persistent high fever (40.1°C), tachycardia, tachypnea, and hypotension, along with markedly elevated inflammatory markers, meeting the diagnostic criteria for septic shock. Laboratory investigations revealed rapid, significant decreases in white blood cell (WBC) count and platelet count. A positive serum EBV viral capsid antigen (VCA) IgM test led to a suspicion of EBV-associated HLH (EBV-HLH). Prior to a definitive diagnosis of EBV-HLH, the patient was initiated on early and adequate combination therapy with corticosteroids and antivirals. This intervention resulted in rapid clinical and laboratory improvement: body temperature normalized by day 3, and peripheral blood counts gradually returned to normal. The subsequent bone marrow aspiration confirmed the HLH diagnosis, supported by elevated serum ferritin and soluble interleukin-2 receptor (sCD25) levels, fulfilling the diagnostic criteria for HLH. The patient was discharged on a tapering regimen of oral methylprednisolone and achieved complete recovery without relapse during follow-up. This case suggests that rapidly progressive and significant leukopenia and thrombocytopenia are key early indicators for distinguishing EBV-HLH from sepsis alone. Early recognition of EBV-HLH and timely initiation of combined corticosteroid and antiviral therapy can effectively control cytokine storm and improve clinical outcomes in patients with favorable treatment responses, providing valuable clinical insights for managing similar severe cases.